2011
DOI: 10.1103/physreve.84.030201
|View full text |Cite
|
Sign up to set email alerts
|

Molten salt eutectics from atomistic simulations

Abstract: Despite their importance for solar thermal power applications, phase-diagrams of molten salt mixture heat transfer fluids (HTFs) are not readily accessible from first principles. We present a molecular dynamics scheme general enough to identify eutectics of any HTF candidate mixture. The eutectic mixture and temperature are located using the liquid mixture free energy and the pure component solid-liquid free energy differences. The liquid mixture free energy is obtained using thermodynamic integration over par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…The characterization of their thermostatic properties is important not only for a fundamental understanding of the physics of ionic liquids at high temperature, but also for energy applications in any system containing a heat storage component. In this respect, it is also important the development of viable simulation methods to determine technological relevant binary and ternary molten salt eutectics 37 . In the following we will calculate, in the liquid phase only, the thermostatic properties of two relevant nitrate molten salt mixed systems: the eutectic and the “solar” mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of their thermostatic properties is important not only for a fundamental understanding of the physics of ionic liquids at high temperature, but also for energy applications in any system containing a heat storage component. In this respect, it is also important the development of viable simulation methods to determine technological relevant binary and ternary molten salt eutectics 37 . In the following we will calculate, in the liquid phase only, the thermostatic properties of two relevant nitrate molten salt mixed systems: the eutectic and the “solar” mixture.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20] Smith and van Gunsteren found that non-linear alchemical coupling not necessarily leads to linear free energy changes. [21] Further applications of al-chemical coupling to the estimation of free energy difference include the free energy of hydration of ions using ab initio molecular dynamics, [22] differences in free energy of binding between various host-guest complexes, [23] free energy differences at phase boundaries to predict melting points, [24,25] the free energy of mixing to identify eutectics in ternary mixtures of molten alkali-nitrate salts, [26] kinetic isotope effects, [27] as well as constraints on the composition of the Earth's core. [28] But also from the solid state point of view the concept of alchemical coupling is used for the prediction of properties of disordered materials, such as co-crystals, solid solutions, or solid mixtures, as a function of molefraction.…”
Section: Common Alchemical Applicationsmentioning
confidence: 99%
“…In order to demonstrate it, the mixed metal salt consisting of the mixture of 12 wt% NaNO 3 and 8 wt% KNO 3 known as "Solar salt" or eutectic mixture [25][26][27] of which the melting point was 495 K, was impregnated onto the MgO because the eutectic composition was difficult to obtain when the coprecipitation method was applied because the filtering and subsequent thorough washing deviated the desired composition. The melting point of NaNO 3 -KNO 3 impregnated on MgO was also determined to be 496 K from differential scanning calorimeter measurement.…”
Section: Resultsmentioning
confidence: 99%